Entrepreneurship as a driver of innovation in the digital age: Analysis of data from 17 ADB regional members - Erkko Autio; Donghyun Park (Asian Development Bank (ADB), 2024)
This paper explores economy- and regional-level determinants of the productivity potential of new entrepreneurial firms using data from Asian Development Bank regional members. Results show that new entrepreneurial firms constitute a highly heterogeneous group in terms of their productivity potential and that this potential is shaped by the economy's national system of entrepreneurship. This system consists of both economylevel institutional conditions, as well as the resource and knowledge dynamics that operate at the level of regional entrepreneurial ecosystems. Economy-level institutional conditions shape the productivity potential of the economy's population of new entrepreneurial firms through their effect on who chooses to become an entrepreneur and what strategic goals the resulting new firms decide and are able to pursue. The regionallevel entrepreneurial dynamics condition the extent to which new entrepreneurial ventures are able to realize this potential through business model innovation. This recognition is important because it suggests that to be effective, an economy's entrepreneurship policy framework needs to address both economy-level institutional conditions as well as regional-level entrepreneurial ecosystem dynamics. The two require different policy approaches and pose distinctive challenges.
Keywords: O30; O38; L26; M13; 330; digital entrepreneurship; productivity; entrepreneurial policy; new firms